2007
DOI: 10.5551/jat.14.86
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pioglitazone Hydrochloride on Japanese Patients with Type 2 Diabetes Mellitus

Abstract: Aim:The effects of pioglitazone hydrochloride monotherapy on abnormal lipid control were evaluated in Japanese patients with type 2 diabetes mellitus, comparing with glibenclamide monotherapy. Methods: Patients were randomly assigned to receive, once daily, pioglitazone hydrochloride, at 15 mg or 30 mg (n 46), or glibenclamide, at 1.25 mg or 2.5 mg (n 46). The 24-week study included patients with type 2 diabetes having high levels of triglyceride (TG). Results: Pioglitazone hydrochloride produced beneficial ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Two studies have described the change of insulin sensitivity after PIO treatment in less obese (but not real lean) diabetes patients. One study found that PIO significantly decreased HOMA-IR [ 16 ], but in another study no significant decrease of insulin resistance was found in non-obese patients even though blood glucose was effectively controlled by PIO [ 17 ]. It may be that the method used for evaluating insulin sensitivity led to the different findings between the two Japanese studies and our study.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have described the change of insulin sensitivity after PIO treatment in less obese (but not real lean) diabetes patients. One study found that PIO significantly decreased HOMA-IR [ 16 ], but in another study no significant decrease of insulin resistance was found in non-obese patients even though blood glucose was effectively controlled by PIO [ 17 ]. It may be that the method used for evaluating insulin sensitivity led to the different findings between the two Japanese studies and our study.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57] Pioglitazone increased HDL-C more so than metformin, 6,9,[12][13][14][15][16]19 rosiglitazone, [55][56][57] and sulfonylureas in pooled analyses. 12,13,50,[58][59][60] For these comparisons, pooled between-group differences ranged from + 0.5 mg per dL to + 4.3 mg per dL. Changes in HDL-C were similar in comparisons of metformin with sulfonylureas or rosiglitazone.…”
Section: Comparative Effects Of Monotherapy Interventions On A1cmentioning
confidence: 96%
“…[44][45][46][47][48] Clinical studies with pioglitazone have shown that this agent may reduce triglyceride levels, elevate HDL-C levels, and improve LDL particle size and susceptibility to oxidation. 49,50 In one clinical study, sitagliptin reduced total cholesterol, triglycerides, and non-HDL-C while increasing HDL-C. 51 Tight glycemic control with insulin may reduce triglyceride levels. 42 In one study, intensive insulin therapy for 4 weeks significantly reduced triglyceride levels (from 260 6 28 mg/dL to 133 6 14 mg/dL; P , 0.001) in individuals with uncontrolled type 2 diabetes on metformin or sulfonylurea monotherapy.…”
Section: Combined Management Of Hyperglycemia and Dyslipidemiamentioning
confidence: 98%